2015
DOI: 10.1631/jzus.b1400203
|View full text |Cite|
|
Sign up to set email alerts
|

Synthetic promoters consisting of defined cis-acting elements link multiple signaling pathways to probenazole-inducible system

Abstract: Probenazole (3-allyloxy-1,2-benzisothiazole-1,1-dioxide, PBZ), the active component of Oryzemate, could induce systemic acquired resistance (SAR) in plants through the induction of salicylic acid (SA) biosynthesis. As a widely used chemical inducer, PBZ is a good prospect for establishing a new chemical-inducible system. We first designed artificially synthetic promoters with tandem copies of a single type of cis-element (SARE, JERE, GCC, GST1, HSRE, and W-box) that could mediate the expression of the β-glucur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…This promoter conferred enhanced sensitivity and significantly higher expression levels in a modified alc gene expression system (Kinkema et al, 2014). Similarly, a strong oxidative stress-inducible promoter (POD) was cloned by Kim et al (2003) from sweet potato, while the study of Zhu et al (2015) revealed a synthetic probenazole (PBZ)-inducible promoter by combining different cis- elements, and its expression pattern in response to multiple signaling pathways such as salicylic acid, jasmonic acid, ethylene, calcium, and mitogen-activated protein kinase (MAPK) was evaluated in Arabidopsis (Zhu et al, 2015). Recently, certain chemically- or pathogen-inducible promoters showed background expression levels in different transgenic plants, making them incompatible tools for biotechnological applications that require inducible expression; however, these results support the development of inducible synthetic promoters in transgenic plants.…”
Section: Functional Characteristics Of the Promoters And Transgenic Pmentioning
confidence: 99%
“…This promoter conferred enhanced sensitivity and significantly higher expression levels in a modified alc gene expression system (Kinkema et al, 2014). Similarly, a strong oxidative stress-inducible promoter (POD) was cloned by Kim et al (2003) from sweet potato, while the study of Zhu et al (2015) revealed a synthetic probenazole (PBZ)-inducible promoter by combining different cis- elements, and its expression pattern in response to multiple signaling pathways such as salicylic acid, jasmonic acid, ethylene, calcium, and mitogen-activated protein kinase (MAPK) was evaluated in Arabidopsis (Zhu et al, 2015). Recently, certain chemically- or pathogen-inducible promoters showed background expression levels in different transgenic plants, making them incompatible tools for biotechnological applications that require inducible expression; however, these results support the development of inducible synthetic promoters in transgenic plants.…”
Section: Functional Characteristics Of the Promoters And Transgenic Pmentioning
confidence: 99%
“…Nitric oxide (NO), salicylic acid (SA), and reactive oxygen species (ROS) are important signal molecules that mediate plant resistance reactions and play important roles in secondary metabolism (Gao et al 2012).The fungal elicitor -induced secondary metabolites accumulation is one of the defense response behaviors. There are a lot of reports stating that the t induction type of plant defense response is dependent on the cross effect between such as SA, JA, ET -signaling pathways to provide one of the best defensive systems , Nair et al 2015, Zhu et al 2015, but the integration of different stress signal and the signal pathways interactions of precise regulation mechanism is still unclear. We summarize several signaling pathways like ion fluxes and Ca 2+ signaling, ROS signaling, JA signaling pathway, SA signaling pathway, NO signaling pathway, other signaling molecules and their crosstalk in the medical plants induced by fungal elicitors is presented in Table 2.The whole process is as shown in Figure 2: Fungal elicitors are identified and combine to receptors selectively on the cell membrane.…”
Section: Signal Transductionmentioning
confidence: 99%
“…Recently, Zhu et al (2015) designed artificially synthetic promoters with tandem copies of cis-elements (SARE, JERE, GCC, GST1, HSRE and W-box) and used the chemical inducer probenazole (PBZ), which is reported to induce systemic acquired resistance (SAR) in plants through the induction of salicylic acid (SA) biosynthesis. Tetramer of each of following cis-elements, SARE, JERE, GCC, GST1, HSRE and W-box showed an enhanced GUS activity by twofold, ninefold, fourfold, twofold, twofold in transgenic Arabidopsis, respectively, under 0.5 mmol/L PBZ treatment.…”
Section: Chemical-responsive Synthetic Promotersmentioning
confidence: 99%
“…4 and Supplementary Table 4). Among all of the synthetic promoters described here, the synthetic promoters 4x SARE, 4 x JERE, 4 x GCC, 4x Gst1, 2x W box were inducible under both pathogen and chemical (probenazole) treatment (Rushton et al 2002, Zhu et al 2015. The synthetic promoters PcCHS-m1, PcCHS-m2, PcH3-7, PcH3-7 m with ACGT-containing elements were responsive to both UV light and pep25 (synthetic peptide elicitor) derived from Phytophthora sojae (Logemann and Hahlbrock 2002) (Supplementary Table 4).…”
Section: Synthetic Promoters Directing Multiple Types Of Expression Imentioning
confidence: 99%